No Access, No Knowledge, or No Interest? Examining Use and Non-use of Assistive Technologies - Brady, Erin; Thies, Bill; Cutrell, Ed (CHI 2014 Workshop on Technology Non-use (CHI 2014 Workshop) Toronto, Canada, 2014)
Assistive technologies can evoke both positive and negative sentiments from users. However, much of the current literature focuses only on adoption, use, and abandonment of assistive technologies, and provides only surface-level explanations for volitional non-use. We summarize a current project that has revealed valuable insights about non-use of assistive technologies by people with visual impairments in the developing world, and discuss some of the difficulties that arise when trying to recruit non-users of assistive technology.